Effect of a soccer ball`s seam geometry on its aerodynamics and trajectory - Goff, J. E.; Hong, S.; Asai, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
Five different soccer balls, each possessing the traditional 32-panel surface design, were tested in a wind tunnel. Only seam depth and width varied between the balls. Wind-tunnel tests and an examination of correlation revealed that seam width with a linear fit R2=0.90 and p<10-4 was a stronger indicator of a ball`s critical speed than seam depth. Wind-tunnel data were used for computational modeling of many soccer-ball trajectories. It was determined that variations in seam geometry resulted in fluctuations up to 4 m in the horizontal range of hard-hit, no-spin kicks that travel approximately 68 m. Those seam geometry variations also contributed to lateral deflections up to 4 m for the aforementioned hard-hit, no-spin kicks.